ANTI-DOPING: THE CREDIBILITY OF THE WHEREABOUTS RULE (The Pretoria Student Law Review, 2021)
In this article, I identify and analyse potential problem areas, from a legal and human rights perspective, regarding the international fight against doping in sport. My focus is specifically on the ‘Whereabouts rule’ laid down by WADA and as enforced in South Africa by the South African Institute for Drug-Free Sport (SAIDS). I begin with an explanation of the Whereabouts rule. This has been necessitated by a large outcry from the media and athletes who not only question its purpose as a doping test but also ask what it is, as a considerable portion of them are yet to be fully enlightened on this WADA 2009 amendment. This theoretical background that I give on the Whereabouts rule is my way of educating my readership and thus living what I preach, as will be evident in my recommendations below, which is mainly the gospel of athletes and media engagement on the Whereabouts rule through education and enlightenment of its content. To enable a deeper understanding of my position on the aforementioned issue, I first define key concepts and acronyms as this will enable me to have a common foundation with the reader, following which I will address the main issue of this article.
Keywords: doping; sport; legal and human rights; South African Institute for Drug-Free Sport; Whereabouts rule